Effect of Microencapsulated Medium-Chain Fatty Acids, Lignocellulose, and Heat-Killed Lactobacillus plantarum L-137 Supplementation on Lactating Sow Performance, and Nutritional and Immunological Parameters in Colostrum - Nithat Wichasit; Wandee Tartrakoon; Rangsun Charoensook; Riantong Singanusong; Juan J. Loor; Gaku Shoji; Satoru Onoda; Tossaporn Incharoen (Veterinary Sciences)
This experiment aimed to evaluate the effects of supplementing miMCFA, lignocellulose, and HKL137 on lactating sow performance and nutritional composition and immunity in colostrum. Fifty 3–4 parity sows (Large White × Landrace) were randomly assigned to one of five treatments: (1) control (CON) without supplementation, (2) miMCFA (S1), (3) miMCFA + lignocellulose (S2), (4) miMCFA + HKL137 (S3), and (5) miMCFA + lignocellulose + HKL137 (S4). Supplements were daily added to the morning meal for 21 days (day 100 of gestation to day 7 post-farrowing). Compared with CON, the S1 and S4 groups had improvements (p < 0.01) in live-born piglet numbers, and colostrum yield. Fat content in colostrum was significantly increased (p < 0.01) in the S3 and S4 groups than those of CON group. Additionally, IgG levels were significantly greatest (p < 0.05) in the S3 and S4 groups. Likewise, IgM levels were notably highest (p < 0.05) in the S2 and S4 groups. These results indicated that the synergistic administration of miMCFA, lignocellulose, and HKL137 resulted in significant enhancements in both sow performance indices and colostrum metrics, encompassing both quantitative and qualitative parameters.